Respuesta :

Answer: 11 degrees

Step-by-step explanation:

            X - 13 = -2

  add 13 to both sides

            X  - 13 = -2

                +13     +13

              X  =  11

Answer:

x  =  13  −  2  =  11 ∘ F

Step-by-step explanation:

Let the original temperature be  

I  =  x .

Final temperature  

F  =  −  2 ∘

Change in temperature  

C  =  I  −  F  =  x  −  ( − 2 )  =  (  x  + 2 ) ∘ F

But it’s given change in temperature  

C  =  13 ∘ F

Therefore,

C  =  13  =  (  x  +  2 )

∴  x  + 2  =  13  or  x  =  13  − 2  =  11 ∘ F

-------------------------------------------------------------------------------------------------

Explanation:

Another way to approach this question, without algebra, is to approach it this way:

We know that at the end of the time period, it's  − 2 ∘ F. At the beginning of the time period, it was  

13 ∘ F warmer. And so we can say that the temperature at the beginning of the time period can be found by adding  − 2  and  13 :

− 2 + 13 = 11 ∘ F